2005
DOI: 10.1111/j.0906-6705.2005.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of epidermal calcium gradient loss and increase in TNF‐α and IL‐1α expressions by glycolic acid in murine epidermis

Abstract: In a previous study, we reported that alpha-hydroxy acids (AHA), such as glycolic acid and lactic acid, did not induce any significant changes in transepidermal water loss for normal murine skin. The ultrastructural observations, however, showed that the extent of lamellar body exocytosis significantly increased. Because AHA can theoretically decrease the calcium ion concentration by chelation, topical AHA may induce the loss of epidermal calcium gradient by lowering the calcium ion concentration in the granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Since the major signaling molecules for GPCRs include intracellular calcium ions, it can be concluded that the change of intracellular calcium ion concentration is a major signal for permeability barrier homeostasis. In addition to the GPCR activation-related calcium modulation, we have also shown that topical application of calcium chelating agents onto normal skin induced the barrier homeostatic responses, including loss of the epidermal calcium gradient and LB secretion 55. Topical application of glycolic acid, which does not induce any changes in TEWL in normal murine skin, significantly increased LB secretion56,57 and an in vitro study using cultured keratinocytes suggests that glycolic acid could lower the calcium ion concentration, at least in part, through its chelating effects on cations, such as calcium ions.…”
Section: Calcium Ions and Barrier Homeostasismentioning
confidence: 94%
“…Since the major signaling molecules for GPCRs include intracellular calcium ions, it can be concluded that the change of intracellular calcium ion concentration is a major signal for permeability barrier homeostasis. In addition to the GPCR activation-related calcium modulation, we have also shown that topical application of calcium chelating agents onto normal skin induced the barrier homeostatic responses, including loss of the epidermal calcium gradient and LB secretion 55. Topical application of glycolic acid, which does not induce any changes in TEWL in normal murine skin, significantly increased LB secretion56,57 and an in vitro study using cultured keratinocytes suggests that glycolic acid could lower the calcium ion concentration, at least in part, through its chelating effects on cations, such as calcium ions.…”
Section: Calcium Ions and Barrier Homeostasismentioning
confidence: 94%
“…Recently, the exposure of various contact allergens is increasing, and because peeling affects the skin barrier, subjects with a history of peeling may have a higher chance of contact sensitization. After peeling, the stratum corneum becomes thinner and shows enhanced desmosomal breakdown on ultrastructural observations (15–17). Protein and messenger RNA expression of tumour necrosis factor‐α (TNF‐α) and interleukin‐1α in murine epidermis was significantly increased after glycolic acid application (17).…”
Section: Discussionmentioning
confidence: 99%
“…After peeling, the stratum corneum becomes thinner and shows enhanced desmosomal breakdown on ultrastructural observations (15–17). Protein and messenger RNA expression of tumour necrosis factor‐α (TNF‐α) and interleukin‐1α in murine epidermis was significantly increased after glycolic acid application (17). TNF‐α and interleukin‐1α appear to be of prime importance in contact sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…[1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [7...…”
Section: Uncited Referencesunclassified